Analysis on Experimental Performance of Hysteretic Behavior of Concrete-Filled Circular CFRP Steel Tubular Beam-Column - Qing-li, Wang; Miao, Chu; Kuan, Peng (Frontiers in Materials, 2022)
in order to study the hysteretic behavior of concrete filled circular CFRP steel tubular Beam-Column under different influence factors, 12 specimens were designed, and the failure mode, middle section lateral force-deflection(P-) curve and middle section bending moment-curvature(M-) curve were studied. Axial compression ratio and longitudinal CFRP reinforcement coefficient as influencing factors, the effects of axial compression ratio and longitudinal CFRP reinforcement coefficient on P- skeleton curve, M- skeleton curve and other indexes were studied; the P- curve and deformation mode of the specimens were simulated by ABAQUS, and the effects of axial compression ratio, slenderness ratio and other main parameters on the hysteretic performance of the members were studied. The results show that CFRP has good lateral restraint and longitudinal reinforcement effect on CFST, and the local buckling of CFST is delayed. The P- curve and M- curve of all specimens are full. The increase of axial compression ratio and longitudinal CFRP reinforcement coefficient can improve the flexural capacity and stiffness of the specimens, and slow down the stiffness degradation. The simulation results are in good agreement with the experimental results. Based on the model analysis of the main parameters, it is found that the increase of steel yield strength and CFRP layers can improve the bearing capacity of the specimens, and the axial compression ratio has the most significant effect on the specimens.